ПУБЛІЧНІ ЗАКУПІВЛІ ЯК ІНСТРУМЕНТ ДЕРЖАВНОЇ ПОЛІТИКИ СПРЯМОВАНОЇ НА ЗАПОБІГАННЯ ТА ЛІКВІДАЦІЮ НАДЗВИЧАЙНИХ СИТУАЦІЙ, В ТОМУ ЧИСЛІ ЕПІДЕМІЙ, НА ПРИКЛАДІ КОРОНАВІРУСНОЇ ХВОРОБИ (COVID-19) - Ustymenko, V.A.; Soshnykov, А.О. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2020)
The article aims to analyze the public procurement implementation within the ordinary conditions as well as the conditions of the prevention and liquidation of emergencies (in a special situation), including epidemics, based on the case study of coronavirus disease (COVID-19). The paper offers suggestions on solving problems in public procurement implementation under conditions of prevention and liquidation of emergencies. To achieve the aforementioned goal, both theoretical (analysis, synthesis, generalization) and empirical (observation and other) methods were used. Additionally, the comparative legal method was used for the analysis of international practices (the World Trade Organization, the European Union) and the experience of the individual EU member states on the implementation of public procurement in the context of tackling the coronavirus disease COVID-19. The article provides an in-depth analysis of the legislation of Ukraine and other countries to formulate an author’s vision of ways how to improve the legal regulation of public procurement aimed at preventing or eliminating emergency situations, in particular epidemics. The authors offer the following: to expand the opportunity of using the negotiated procedure for the procurement of supplies, works or services that are necessary not only to eliminate emergencies, but also to prevent them; to empower the Cabinet of Ministers of Ukraine and the National Security and Defense Council of Ukraine to introduce the negotiated procedure for the procurement of supplies, works and services in case of special conditions; to reduce the time for the negotiated procedure implementation (up to 1 day) when emergency or pressing need purchase is necessary (for example, to prevent an epidemic); to grant the right to the Cabinet of Ministers of Ukraine to establish a list of supplies, works or services for which one hundred percent prepayment may be provided in procurement contracts. REFERENCES